AUTONOMOUS VEHICLES: TECHNICAL SAFETY AND ALGORITHMIC CHALLENGES (International journal of artificial intelligence, 2026)
Autonomous vehicles (AVs) represent a revolutionary shift in transportation technology. However, ensuring their technical safety and algorithmic reliability remains a key challenge. This paper analyzes the architecture of autonomous driving systems, focusing on sensor fusion, AI decision-making algorithms, and safety validation frameworks.